PENGARUH PROFITABILITAS, RESIKO BISNIS, LIKUIDITAS DAN TANGIBILITY TERHADAP STRUKTUR MODAL - Widya Nengsih, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to analyze and examine the effect of profitability, business risk, liquidity and tangibility on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2015-2017. Samples taken using purposive sampling method. Sampling of manufacturing companies that meet the criteria for use in this study are 66 companies. The test in this study consisted of descriptive statistical analysis, common effect model test, fixed effect model test, random effect model test, chow test, hausman test, F test, t test and coefficient of determination test. The results of the t test using Eviews version 10 show that profitability and liquidity have a significant effect on capital structure. Business risk and tangibility have no significant effect on capital structure. the results of the F test obtain results that are all independent variables simultaneously influencing the capital structure as the dependent variable.